2015
DOI: 10.1177/0956462415573122
|View full text |Cite
|
Sign up to set email alerts
|

Complementary medicine use by people living with HIV in Australia – a national survey

Abstract: Little is known about the use of complementary medicines by people living with HIV in Australia since the advent of more effective combination antiretroviral therapy. We conducted an anonymous survey of 1211 adult patients receiving combination antiretroviral therapy from one of eight specialist HIV clinics across Australia, aiming to identify the current patterns of use of ingestible complementary medicines. Data collected included reasons for use, information sources and rates of disclosure of use of complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…‐ 8 , 16 , 17 People with chronic diseases or comorbidities such as cancer, diabetes, musculoskeletal disorders or mental illness frequently use complementary medicines 16 . A study of 10 011 Australian women aged 59–64 years found that 39% of those with menopausal symptoms consulted complementary medicine practitioners, and that 75% used self‐prescribed complementary therapies; 18 53% of 1037 people with HIV attending specialist clinics also used complementary medicines 19 . As many as 65% of Australian people with cancer in 2010 used some form of complementary medicine, more than half of whom did so in combination with conventional therapy 20 .…”
Section: Trends In Usementioning
confidence: 99%
See 1 more Smart Citation
“…‐ 8 , 16 , 17 People with chronic diseases or comorbidities such as cancer, diabetes, musculoskeletal disorders or mental illness frequently use complementary medicines 16 . A study of 10 011 Australian women aged 59–64 years found that 39% of those with menopausal symptoms consulted complementary medicine practitioners, and that 75% used self‐prescribed complementary therapies; 18 53% of 1037 people with HIV attending specialist clinics also used complementary medicines 19 . As many as 65% of Australian people with cancer in 2010 used some form of complementary medicine, more than half of whom did so in combination with conventional therapy 20 .…”
Section: Trends In Usementioning
confidence: 99%
“…specialist clinics also used complementary medicines. 19 As many as 65% of Australian people with cancer in 2010 used some form of complementary medicine, more than half of whom did so in combination with conventional therapy. 20 A similar finding was made in a study of 4500 Australians aged 50 years or more; 46.3% of the participants used complementary medicines, of whom 87.4% used them alongside conventional therapy.…”
Section: Trends In Usementioning
confidence: 99%
“…CM are also known as 'traditional' or 'alternative' medicines and include substances such as vitamins, minerals, herbal remedies, aromatic oils and homeopathic products [49]. The use of CM among PLHIV is common [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. In a recent survey of Australians living with HIV (n=1211), 53% of respondents reported they had used one or more CM in the 12 months prior to the study, 50% in the previous week [52].…”
Section: Introductionmentioning
confidence: 99%
“…However, this study did not specifically seek views of HIV positive individuals. Studies that have explored CM use among PLHIV have mainly focused on providing prevalence data [51][52][53][54][55][56][57]61,65], while those that have sought to understand the beliefs underpinning use have been conducted overseas in countries that may differ from Australia in areas such as access and cultural norms [62,65]. Of the limited number of studies that sought to understand motivation for CM use among PLHIV in Australia, the majority involved small participant numbers [53,58,64].…”
Section: Introductionmentioning
confidence: 99%
“…The most common uses of CAM reported by PLWH were for general well-being, to increase immune function, to reduce side-effects of ART, and to address comorbid disorders. 9,10 Generally, PLWH have reported various benefits from CAM use, and health risks associated with the majority of CAM treatment options have been relatively rare. 11 Patients have also reported that CAM helped them cope with their HIV diagnosis, increased their feeling of control, and improved HIV treatment outcomes.…”
mentioning
confidence: 99%